Penatalaksanaan Penyakit Tuberkulosis dengan Diabetes Melitus pada Wanita Usia 64 Tahun Melalui Pendekatan Kedokteran Keluarga - Iqbal Lambara Putra; Azelia Nusadewiarti; Winda Trijayanthi Utama (MAJORITY, 2020)
The elderly group is included in the vulnerable population because of the process of decreasing the ability to avoid disease and exposure to risk factors for chronic diseases such as Diabetes Mellitus (DM). DM can increase the risk of tuberculosis (TB) infection three times greater than the normal population, and can also increase the risk of reactivation of TB and latent TB. The study conducted was a case report. This case report aims to implement evidence-based medicine-based family doctor services to patients by identifying risk factors, clinical problems, and management with a patient-centered approach and a family approach. Primary data were obtained through anamnesis and physical examination by making home visits, filling in family folders, and filling in patient files.